Thermodynamic, exergetic, and thermoeconomic analyses of a 1-kW proton exchange membrane fuel cell system fueled by natural gas. (15th February 2021) - Seo, Seok-Ho; Oh, Si-Doek; Park, Jinwon; Oh, Hwanyeong; Choi, Yoon-Young; Lee, Won-Yong; Kwak, Ho-Young
Abstract: In this study, thermodynamic, exergetic, and thermoeconomic analyses of a 1-kW proton exchange membrane fuel cell (PEMFC) fueled by natural gas were performed. In particular, the chemical reaction rates of the burner, reformer, water gas shift (WGS) reactor, and preferential oxidation reactor (PrOx) were carefully investigated to obtain the range of rates of the reforming and WGS reactions. The unit cost of H2 gas produced by the fuel processing unit, and of the electricity generated by the PEMFC system were determined using the unit cost of H2 by a detailed thermoeconomic analysis based on the data obtained from a series of experiments. In the presence and absence of an anode-off gas in the burner, the unit costs of the H2 produced by the fuel processing unit were approximately 22.8 $/GJ and 27.5 $/GJ, respectively, considering the unit cost of natural gas, 10 $/GJ. Correspondingly, the calculated unit costs of electricity produced by the PEMFC were 286.8 $/GJ and 295.6 $/GJ, respectively. Highlights: Thermodynamic, exergetic and thermoecnomic study was conducted for a 1-kW PEMFC based on experimental data. Detailed chemical reactions in the fuel processing unit in the PEMFC was done. Range of reaction rates for reforming and water gas shift reactions was obtained. Unit cost of hydrogen with and without anode-off gas was obtained. Unit cost of electricity with and without anode-off gas was obtained using the obtained hydrogen unit cost.